The Key to Successful Care Coordination and Patient-Centeredness in Cardiac Surgery - Hari Hendriarti Satoto; Ferdi Antonio; Annisa Zakia Widiastuti (Jurnal Kesehatan Masyarakat, 2025)
In the healthcare sector, delivering patient-centered care is vital for enhancing results and ensuring favorable experiences for individuals. Coordinating care plays a critical part in attaining patient-centricity by enabling smooth and efficient interaction and partnership among healthcare professionals, patients, and their families. Efficient care coordination advances patient-centered care by guaranteeing that all aspects of a patient's medical journey are interconnected and tailored to address their specific requirements. This connectivity and personalization can be accomplished through various approaches such as evidence-based practice, electronic medical records utilization, promotion of patient safety, cross-functional teamwork, mutual communication, goal alignment, and shared accountability. Achieving efficient care coordination for cardiac surgery involves assembling a varied team that collaborates to develop personalized treatment plans for every patient. This approach ensures the smooth coordination of all elements of patient care, including pre-operative assessments, surgical procedures, and post-surgery rehabilitation plans. Prioritizing the significance of coordinated care in hospital administration can assist policymakers and healthcare systems in striving to deliver tailored, patient-focused care that contributes to enhanced health results for individuals. Through enhancing communication and teamwork, distributing tasks equitably, and advancing evidence-based practices among medical professionals, the overall coordination of care in cardiac surgery can be notably enhanced resulting in improved personalized patient care and ultimately better health outcomes.